Interaction of pathogenic fungi with host cells: Molecular and cellular approaches - Mendes-Giannini, Maria José Soares [UNESP]; Soares, Christiane Pienna [UNESP]; da Silva, J. L. M.; Andreotti, P. F. (Elsevier B.V., 2005)
This review provides an overview of several molecular and cellular approaches that are likely to supply insights into the host-fungus interaction. Fungi present intra- and/or extracellular host-parasite interfaces, the parasitism phenomenon being dependent on complementary surface molecules. The entry of the pathogen into the host cell is initiated by the fungus adhering to the cell surface, which generates an uptake signal that may induce its cytoplasmatic internalization. Furthermore, microbial pathogens use a variety of their surface molecules to bind to host extracellular matrix (ECM) components to establish an effective infection. on the other hand, integrins mediate the tight adhesion of cells to the ECM at sites referred to as focal adhesions and also play a role in cell signaling. The phosphorylation process is an important mechanism of cell signaling and regulation; it has been implicated recently in defense strategies against a variety of pathogens that alter host-signaling pathways in order to facilitate their invasion and survival within host cells. The study of signal transduction pathways in virulent fungi is especially important in view of their putative role in the regulation of pathogenicity. This review discusses fungal adherence, changes in cytoskeletal organization and signal transduction in relation to host-fungus interaction. (c) 2005 Federation of European Microbiological Societies. Published by Elsevier B.V. All rights reserved.
Keywords: fungi; mycosis; fungal virulence; fungal pathogenesis; interaction fungi-host cells; signaling